2020
DOI: 10.31557/apjcp.2020.21.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ki-67 and Βeta-Catenin in Pseudoepitheliomatous Hyperplasia and Squamous Cell Carcinoma in Oral Mucosal Biopsies : An Immunohistochemical Study

Abstract: Objective: To examine the immunohistochemical expression of Ki-67 and beta-catenin in pseudoepitheliomatous hyperplasia and squamous cell carcinoma (SCC) in oral mucosal biopsies. Methods: In this comparative cross sectional study, 70 cases of each PEH and OSCC were taken from the patients of both genders and in all age groups. Study was conducted at Armed Forces Institute of Pathology (AFIP), Rawalpindi from Dec 2017 to March 2019. Statistical analysis was done with the help of SPSS Version 24.0. We used Chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…As indicated by our examination and past investigations performed by Raju et al ,[ 22 ] Dragomir et al ,[ 23 ] and Ahmad et al ,[ 24 ] Ki‑67 ends up being helpful in surveying tumor aggressiveness. Increased cellular proliferation is associated with more advanced lesions, and the distribution of proliferating cells in tissues may disclose about the regulatory mechanisms that become dysfunctional through carcinogenesis.…”
Section: Discussionsupporting
confidence: 69%
“…As indicated by our examination and past investigations performed by Raju et al ,[ 22 ] Dragomir et al ,[ 23 ] and Ahmad et al ,[ 24 ] Ki‑67 ends up being helpful in surveying tumor aggressiveness. Increased cellular proliferation is associated with more advanced lesions, and the distribution of proliferating cells in tissues may disclose about the regulatory mechanisms that become dysfunctional through carcinogenesis.…”
Section: Discussionsupporting
confidence: 69%
“…While surgical and chemotherapy strategies to treat OSCC have improved significantly, the diagnosis and prognosis of OSCC patients require further investigation. Numerous studies have indicated that cancer cell mutations can promote cell proliferation and metastasis in several cancer types, including OSCC [15,16]. Wnt/β-catenin signaling was shown to play a vital role in the tumorigenesis of malignant tumors which promoted an investigation into whether βcatenin was expressed in the nucleus of OSCC cells [6,17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to explore the correlation between β-catenin and Notum in OSCC. Studies have shown that β-catenin is expressed in OSCC tissue [30]. However, its mechanism of action is unclear.…”
Section: Discussionmentioning
confidence: 99%